Chemical composition and antioxidant activity of Campanula alliariifolia - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2008)
In this study, the chemical constituents of Campanula alliariifolia Willd. (Campanulaceae) are being investigated for the first time with the aid of this article. Five known compounds, which were quercetin-3-O-glucoside, quercetin-3-O-rutinoside, kaempferol-3-O-glucoside, lobetyolin (9-O--D-glucopyranosyl-2,10-tetradecadien-4,6-diyne-8,14-diol) and lobetyol (2,10-tetradecadien-4,6-diyne-8,9,14-triol), were isolated from the methanol extract. The antioxidant activity of the methanol extract and the purified compounds of the plant was investigated with DPPH (1,1-diphenyl-picrilyhydrazyl) (free radical scavenging activity) and reducing power methods. The methanol extract has antioxidant capacity according to the mentioned methods. Lobetyol and lobetyolin showed significant antioxidant activity more than both methanol extract and other purified compounds.
Keywords: campanula alliariifolia; DPPH; reducing power; polyacetylene; LOBELIA-INFLATA; ROOTS